Validation of a risk prediction model for endometrial carcinoma among postmenopausal women in Sri Lanka - Withanage Iresha Udayanagani Jayawickrama; Chrishantha Abeysena (Journal of the College of Community Physicians, 2022)
Introduction: A risk prediction model was developed to predict the risk of developing endometrial carcinoma among postmenopausal women. It is strongly recommended to evaluate the performance of the risk prediction model by external validation before using it in the community.